Pengaruh Lingkungan Kerja, Kompensasi, dan Pelatihan Terhadap Kinerja Karyawan - Nurrahma, Adynda (Journal of Business and Economics Research (JBE), 2025)
Employee performance is one of the main factors that determine the success of an organization, especially in the highly competitive telecommunications industry. At PT X, employee performance is influenced by various factors, including work environment, compensation, and training. Therefore, this study aims to analyze the effect of work environment, compensation, and training on employee performance of PT X. The population in this study were all employees of PT X, with a sample of 100 respondents using random sampling technique. Data was collected through questionnaires distributed directly and online. The data analysis method used is multiple linear regression analysis with SPSS 27. Results The results showed that the work environment partially positive and significant on the performance of employees of PT X. Compensation partially has a positive and significant effect on the employee performance of PT X. Training partially has a positive and significant effect on employee performance of PT X. And the work environment, compensation, and training together have a positive and significant effect on the performance of employees of PT X